Role of purinoreceptors in the release of extracellular vesicles and consequences on immune response and cancer progression - Thomas Duret; Mohammed Elmallah; Jérôme Rollin; Philippe Gatault; Lin-Hua Jiang; Sébastien Roger (Biomedical Journal, 2025)
Cell-to-cell communication is a major process for accommodating cell functioning to changes in the environments and to preserve tissue and organism homeostasis. It is achieved by different mechanisms characterized by the origin of the message, the molecular nature of the messenger, its speed of action and its reach. Purinergic signalling is a powerful mechanism initiated by extracellular nucleotides, such as ATP, acting on plasma membrane purinoreceptors. Purinergic signalling is tightly controlled in time and space by the action of ectonucleotidases. Recent studies have highlighted the critical role of purinergic signalling in controlling the generation, release and fate of extracellular vesicles and, in this way, mediating long-distance responses. Most of these discoveries have been made in immune and cancer cells. This review is aimed at establishing the current knowledge on the way which purinoreceptors control extracellular vesicle-mediated communications and consequences for recipient cells.